2017
DOI: 10.1002/2016jb013924
|View full text |Cite
|
Sign up to set email alerts
|

Rapid rupture directivity determination of moderate dip‐slip earthquakes with teleseismic body waves assuming reduced finite source approximation

Abstract: For an earthquake with along‐dip rupture, there is opposite directivity effects on downgoing direct P wave and upgoing depth phases (pP and sP), and this can be exploited for resolving fault plane and rupture direction. We propose a method to calculate the reduced finite source synthetics for teleseismic P wave and determine the rupture directivity via waveform fitting. We verified the effectiveness of this method with forward tests and investigated its robustness against station selection, uncertainties in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Note that our technique does not assume horizontal rupture, but instead solves for the rupture dip angle as a free parameter. However, a complete resolution of the rupture dip requires station coverage with a wide range of ray takeoff angles (Abercrombie, Poli, & Bannister, 2017; He & Ni, 2017; Park & Ishii, 2015), which is a condition that is rarely met for our data set. Because of this issue, uncertainties in dip direction are substantially larger than those for strike (where prior knowledge from moment tensor solutions provides additional constraints).…”
Section: Resultsmentioning
confidence: 99%
“…Note that our technique does not assume horizontal rupture, but instead solves for the rupture dip angle as a free parameter. However, a complete resolution of the rupture dip requires station coverage with a wide range of ray takeoff angles (Abercrombie, Poli, & Bannister, 2017; He & Ni, 2017; Park & Ishii, 2015), which is a condition that is rarely met for our data set. Because of this issue, uncertainties in dip direction are substantially larger than those for strike (where prior knowledge from moment tensor solutions provides additional constraints).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have included other information, such as depth phases (e.g. He & Ni, 2017), to help constrain these cases, but in general it is a challenge common to all directivity analyses.…”
Section: Assumptions and Interpretability Of Resultsmentioning
confidence: 99%
“…It should be understood that this results from a lack of sensitivity to along‐dip ruptures. Some studies have included other information, such as depth phases (e.g., He & Ni, ), to help constrain these cases, but in general, it is a challenge common to all directivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the dipping direction remains unresolved from this method, which could be due to the similar dip angles of the two nodal planes as suggested in He and Ni (2017). With the constraint from near-field strong motion, Taymaz et al (2022) suggested a north-dipping model with updip and westward propagation of the bilateral rupture pattern could best fit teleseismic waveforms and well explain the aftershock distributions.…”
Section: Aftershock Distribution and Source Geometriesmentioning
confidence: 90%
“…In addition, we adopted the reduced finite source method (He & Ni, 2017) to constrain the rupture directivity parameters. In this algorithm, teleseismic P waves are decomposed into down‐going waves (P and SP) and upgoing waves (pP and sP).…”
Section: Aftershock Distribution and Source Geometriesmentioning
confidence: 99%